2010
DOI: 10.1111/j.1745-4530.2008.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Caffeine From Tea Waste Using Subcritical Water Extraction

Abstract: The aim of this study was to investigate the isolation of caffeine from tea waste using subcritical water extraction (SCWE) method. The effect of various operating conditions such as water temperature (100,125,150, 175 and 200C), water flow rate (1, 2 and 4 g/min), mean particle size (0.25, 0.5, 1 and 2 mm) and pressure (20, 30 and 40 bar) on extraction yield and rate were determined. SCWE at 175C, water flow rate of 4 g/min and mean particle size of 0.5 mm was found to be able to recover 0.77% (w/w) of caffei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…The high coefficient of temperature indicates that the temperature has the greatest effect on the extraction of total polyphenol. The same results were found by Shalmashi, Abedi, Golmohammad, and Eikani () from green tea waste. The probable reason for the significant increase of the TP amount at 150°C was the reduction in the dielectric coefficient of water at high temperatures and better phenolic extraction (Cheigh, Yoo, Ko, Chang, & Chung, ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The high coefficient of temperature indicates that the temperature has the greatest effect on the extraction of total polyphenol. The same results were found by Shalmashi, Abedi, Golmohammad, and Eikani () from green tea waste. The probable reason for the significant increase of the TP amount at 150°C was the reduction in the dielectric coefficient of water at high temperatures and better phenolic extraction (Cheigh, Yoo, Ko, Chang, & Chung, ).…”
Section: Resultssupporting
confidence: 88%
“…Hence, temperature was the main factor in the SWE of the phenolic compounds. Same results were obtained by Zhang et al (), Singh and Saldana (), and Shalmashi et al (). According to other investigations, this happened because of the diminution of the water dielectric constant due to the high temperature close to the dielectric constant of ethanol or methanol, leading to the inducement of the polyphenol's solubility (Rodriguez‐Meizoso et al, ).…”
Section: Resultssupporting
confidence: 85%
“…It was reported that the percentage yield of caffeine extracted by subcritical water extraction from tea waste increased depending on the increase in the extraction temperature from 100 to 175°C. The highest value was obtained at 175°C was 0.77% (w/w) (Shalmashi, Abedi, Golmohammad, & Eikani, 2010). This difference might be due to the fact that most of the caffeine is contained in CS could be extracted even at 25°C, although caffeine in tea waste is located in an area where it can be extracted due to the degradation of cell walls and other cell components (Table 2).…”
Section: Hplc Of Caffeine 5-cqa and 5-hmf Of Cs Extractsmentioning
confidence: 74%
“…For example, SWE has been employed to extract caffeine from tea or tea waste [72,73]. The SWE technique uses hot water at temperatures ranging from 100 to 3741C under high pressures from 10 to 60 bar [71].…”
Section: Other Extraction Techniquesmentioning
confidence: 99%